1956
DOI: 10.6028/jres.057.017
|View full text |Cite
|
Sign up to set email alerts
|

Purification of substances by a process of freezing and fractional melting under equilibrium conditions

Abstract: .\ purifi cation tec hnique has been developed wh ereby a mass of well -defined crystals, form ed by slow cr ystall izat ion of a liquid, . is melted under eq uilibrium co nditi ons into a seri es of fract ions. In this process the entire mass of t he s ubsta nce is fra ctio nated into its g ross impurities and high-purity material. This offers di stinct advantages over co nv ent ional fra ctional crystallization tec hniques. The apparatus prov ides for co ndu ct in g the fr actionat ing process in a closed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1958
1958
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Freezing desalination process mainly depends on a seawater phase change process from the liquid phase to the solid phase "ice". In theory, most ice crystals contain pure water [9] and [10]. Hence, fresh water can be extracted from the formed ice after the complete freezing process while the salt is disposed as a high concentration brine.…”
Section: Introductionmentioning
confidence: 99%
“…Freezing desalination process mainly depends on a seawater phase change process from the liquid phase to the solid phase "ice". In theory, most ice crystals contain pure water [9] and [10]. Hence, fresh water can be extracted from the formed ice after the complete freezing process while the salt is disposed as a high concentration brine.…”
Section: Introductionmentioning
confidence: 99%
“…Finally nitrobenzene has been investigated as a typical substance with a large dipole moment. All compounds were distilled, dried with silica gel, and finally purified under vacuum conditions by the fractional melting technique [12]. The two samples analyzed for each compound (except 2-methylnaphthalene) represent the pure fraction and the reject fraction obtained by this technique.…”
Section: Results Of Purity Analysesmentioning
confidence: 99%
“…Previous investigations on purification by the fractional crystallization and melting process reported from the NBS [1] indicated that with some substances a major portion (about ¾) of the impurities is removed along with the first 20-percent fraction melted. The following successive 20-percent fraction melted removed about of the remaining impurities.…”
Section: Preparation Of the Samplesmentioning
confidence: 99%
“…A preliminary determination of the purity of the difluoro sample before purification gave 99.7 mole percent. With a starting material of this purity, the last 40-percent fraction melted was expected to be 99.95 mole percent pure if the efficiency reported in reference [1] were achieved.…”
Section: Preparation Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation